Pre-ipo characteristics and post-ipo operating performance in Malaysia / Catherine S F Ho and Raja Aerol Shariza Raja Amir Hamzah - S F Ho, Catherine; Raja Amir Hamzah, Raja Aerol Shariza (Institute of Business Excellent (IBE), 2011)
The performance of Initial Public Offerings (IPO) has been investigated in numerous studies but little attention has been paid to shed more light on the factors that influence the success of these IPOs. This paper investigates the relation between pre-IPO characteristics and post-IPO operating performances. The objective of this study is to identify the determinants of post IPO operating performance. The pre-IPO factors include pre-IPO profitability, dilution of ownership, age and size of firm. The post-IPO operating performances include: return on asset, return on sales and asset turnover. Using newly public-listed companies on the Main Board of Bursa Malaysia from 2000 to 2004, findings confirmed that pre-IPO profitability and firm size are the key predictors of post-IPO performance. The results obtained provide useful information and caution for prospective investors in new issues.